Efeito da estimulação de acupontos em pacientes com lombalgia crônica inespecífica : ensaio clínico randomizado - Mendonça, Andreza Carvalho Rabelo (2017)
Low back pain (LBP) is one of the most common symptoms in clinical practice, occurring in more than 85% of individuals at some time in their lives, there is enormous economic pressure to provide rational and efficient care for this type of patient. For years man has been researching ways to relieve low back pain; This has provided advances in the field of analgesic modalities, among them the adoption of acupuncture. Thus, the objective of the present study was to evaluate the effect of acupuncture in the treatment of non-specific chronic low back pain (LCI). It is a randomized, double-blind, placebo-controlled clinical trial. 18 subjects were allocated in the Real Acupuncture group (RA) and 17 in the Acupuncture group Placebo (AP). Subjects were treated three times a week, every other day, totaling 10 visits. The study variables and their respective measurement : pain intensity at rest and in movement (numerical scale of 11 points), characterization of pain (McGill pain questionnaire), catastrophic pain (Pain Catastrophic Scale), (Fear Avoidance Beliefs Questionnaire-FABQ), muscle strength (dynamometer), functional (threshold of pressure pain threshold (algometer), sensory threshold (von Frey filaments), central sensitization (pain modulation and temporal summation) Oswestry Disability Index (ODI and Roland Morris Disability Questionnaire - QIRM), fear of moving (Tampa Kinesiophobia Scale) and quality of life (EQ-5D). In the personal characteristics and demographic partners, no significant differences were found between the groups; After each of the 10 sessions, the pain intensity was significantly lower at rest (p <0.028) and in movement (p <0.035) in the RA group. In the AP group, pain intensity at rest (p = 0.008) and movement (p = 0.038) were significantly lower after 10 sessions. There was a significant reduction in the number of words chosen (NPE; Br-MPQ) in the RA group when comparing sessions 1 and 10 (p = 0.004). And there was a significant decrease in NPE between 1st and 10th in the AP group (p = 0.017). Regarding the pain classification index (DCI), there was a significant reduction (p = 0.001) when comparing the 1st and 10th sessions in the RA group. When comparing the RA and AP groups, the only significant difference was that the LSC of the right lumbar was significantly lower in the RA group than in the AP group before the 1st session (p = 0.026). In the ST test, the intensity of pain in the second 1, 10, 20 and 30 did not decrease significantly after the 10 sessions in any of the groups. In the MCD, the LDPs of the moments before, during and after the test were not significantly different in the comparison of the 1st to the 10th session, no in the intergroup comparison. The muscle strength of the RA and PA groups did not change significantly. There was no significant difference in the impact of pain on the functionality in the RA group before and after treatment, whereas in the AP group before and after the therapy, a significant difference was observed (p = 0.015). The same occurred for functional disability in session 1 and session 10. The catastrophic pain, kinesiophobia and FABQ physical activities and work did not present statistically significant alteration after the 10 sessions in both groups. The intensity of discomfort of the patients at the time of puncture assessed through the EN of 11 points did not differ significantly during the treatment in both groups. In the present study, the effect of acupuncture on the treatment of CLI in the RA group decreased the intensity of pain after each session, the NPE and the DCI in the measurement of pain. However, there was no evidence of improvement in sensory tests, other functional aspects, psychoemotional aspects and quality of life. In the AP group, the pain intensity at rest and in movement before the 1st and after the 10th session decreased and also the NPE decreased, and in the functional aspects there was decrease of the impact of the pain in the functionality only.